Lựa chọn ngành học tác động thế nào đến tiền lương của sinh viên sau khi ra trường? Bằng chứng từ Việt Nam - Nguyễn Hà Đăng, Khoa (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
This paper investigates the effect of major choice on students’ earnings after they have graduated. Using Data from the “Labour Force Survey 2019”,the author focuses on young graduates group who are from 21 to 33 years old. The study applied the Heckman model in which the Inverse Mills Ratio is added as a solution to the problem of “selection bias”. This bias is caused by the unobserved wages of those who do not work. The Heckman model helps estimate the earnings equation and explains the decision to participate in the labour market of workers. It can be seen from the results that university degrees positively influence youngsters’ decision to work. Results from the observed earnings equation show that graduates who study Biology, Agriculture, Law,and Education see their earnings after school less than their Engineer & Technology major base group by 8.1%, 12.4%, 12.1%, and 6.2%. On the other hand, young graduates in Defense & Security and Creative Art & Design gain earnings than the base group at 16.5% and 7.0%, respectively.
Keywords: Wage; Heckman selection model